ANALISIS BIBLIOMETRIK : PEMETAAN TREN RISET KOHESIVITAS TIM DALAM OLAHRAGA - Izdihar, Siti Dhiya; Liche Seniati, Ali Nina; Guritna, E. Taru (Institut Teknologi Bandung, 2026)
This study presents a bibliometric analysis of research trends on team cohesion in sports. Data were retrieved from the Scopus database, covering 288 journal articles published between 1992 and 2024. The analysis examined publication trends, citation patterns, influential articles, leading journals, and keyword structures. The findings indicate a significant increase in research output after 2016, with a peak in 2024, highlighting team cohesion as a key psychosocial construct associated with performance, group dynamics, and athlete functioning. Keyword mapping identified four major thematic clusters: performance, group dynamics, methodology, and athlete characteristics. This study provides a comprehensive overview of the intellectual structure of team cohesion research and offers directions for future studies and practical applications in sport psychology.